2018
DOI: 10.1016/j.system.2018.03.008
|View full text |Cite
|
Sign up to set email alerts
|

A mixed-methods study of the impact of sociocultural adaptation on the development of pragmatic production

Abstract: A mixed-methods study of the impact of sociocultural adaptation on development of pragmatic production This study employs a mixed-method research approach to investigate the effect of sociocultural adaptation on the development of pragmatic production in a study abroad (SA) context. It focuses on the ability to produce pragmatic routines, and whether sociocultural adaptation experiences by learners of different cultural backgrounds predict pragmatic gains. Seventy-eight college students participating in SA pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…The small number of previous studies addressing the association between sociocultural adaptation and pragmatic development has revealed mixed findings. This study is in line with previous investigations reporting a significant influence (Schmidt, 1983;Dörnyei et al, 2004;Sánchez-Hernández, 2018a; forthcoming 2018b), while it is inconsistent with works that have observed a non-significant (Shively & Cohen, 2008) or partial influence (Taguchi, 2014). Moreover, the study adds to the existent picture the finding that sociocultural adaptation and subsequent L2 pragmatic awareness are enhanced not only by contact with NSs but also by support from co-nationals.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The small number of previous studies addressing the association between sociocultural adaptation and pragmatic development has revealed mixed findings. This study is in line with previous investigations reporting a significant influence (Schmidt, 1983;Dörnyei et al, 2004;Sánchez-Hernández, 2018a; forthcoming 2018b), while it is inconsistent with works that have observed a non-significant (Shively & Cohen, 2008) or partial influence (Taguchi, 2014). Moreover, the study adds to the existent picture the finding that sociocultural adaptation and subsequent L2 pragmatic awareness are enhanced not only by contact with NSs but also by support from co-nationals.…”
Section: Discussionsupporting
confidence: 76%
“…Matsumura, 2008;Bardovi-Harlig & Bastos, 2011;Taguchi et al, 2013). Nevertheless, very few ILP studies have focused on the variable of intercultural competence (exceptions include Taguchi, 2015;Sánchez-Hernández, 2018a), and even less have explored L2 pragmatic development in relation to both intensity of interaction and intercultural competence (with the exception of Shively & Cohen, 2008;Taguchi et al, 2016).…”
Section: L2 Pragmatic Development In Relation To Intercultural Competmentioning
confidence: 99%
“…For instance studies conducted by Kim and Taguchi (2016) and Taguchi and Kim (2014) showed that tasks could be set for students to perform PDR-high or PDR-low speech acts by optimizing interaction between learner and learner under teacher's guidance in order to learn both sociopragmatic and pragmalinguistic features (Kim & Taguchi, 2016;Taguchi & Kim, 2014). Some findings of the studies show that explicit or implicit teaching of pragmatic aspects may help learners to socialize or familiarize themselves to the aspects by the help of their teachers and their peers (Alsuhaibani, 2020;Lantz-Andersson, 2017;Sánchez-Hernández, 2018;Sydorenko, Daurio, & L. Thorne, 2017;Taguchi, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, an interpretation will be conducted between qualitative and quantitative data. 49 …”
Section: Methods and Analysismentioning
confidence: 99%
“…Finally, an interpretation will be conducted between qualitative and quantitative data. 49 Patient and public involvement Children with cancer, legal guardians and their healthcare professionals have been involved in the development of the PicPecc tool. 34 Healthcare professionals have been involved in the development of the hybrid design, in order to optimise the feasibility of the study.…”
Section: Process Evaluationmentioning
confidence: 99%